Forming a healthy lifestyle among students (Eurasian Research Bulletin, 2023)
In the independent development of the Republic of Uzbekistan, it is important to build an economic-democratic society, to renew the spirit of society, to achieve high results in the spheres of state and social construction, to promote a healthy lifestyle, to protect the health of the young generation and the entire nation. Promotion of a healthy lifestyle should be carried out in different directions. On the one hand, it is aimed at providing students and adults with certain medical and hygienic knowledge about healthy living, awakening their imagination about how a healthy lifestyle affects the development of the organism, and on the other hand, it depends on the achievement of hygienic rules in education, the formation of skills to make it a habit to take care of the health of oneself and the people around. In this regard, it is necessary to promote a healthy lifestyle in mass media, in lyceums and colleges in cooperation with all educational institutions.